SERO Suicide Prevention App: A Preliminary Study of User Experiences in Real World - Kerstin DENECKE; François VON KAENEL; Caroline GURTNER; Michael DURRER (Applied Medical Informatics)
The study’s objective is to explore users’ experiences with the SERO app, a suicide prevention app. Its main functionalities include a self-assessment tool, safety plan, information and contact numbers that can be personalized. To collect the experiences, all registered users were contacted by E-mail and asked to fill a questionnaire with 3 open-ended questions and 2 questions with predefined answers. 74 persons answered the questionnaire. Generally, they confirmed that the app is easy to use and particularly the safety plan and self-assessment tool were very much appreciated. The responses were valuable to learn about the challenges of users in benefiting from the app usage, which is providing sufficient guidance for developing safety strategies.